Reação de híbridos de milho à mancha-de-macrospora - Piletti, Giovani Jian (2014)
Macrospora leaf spot, caused by the fungus Stenocarpella macrospora, has shown to be frequent and important among corn fields in Brazil. Genetic resistance is one of the main strategies to control corn leaf diseases. In Brazil, there is scarce information on the resistance of hybrids to Stenocarpella macrospora. The aim of this study was to evaluate the reaction of 25 corn hybrids to macrospora leaf spot. The experiment was conducted in 2011, in a greenhouse under controlled temperature and relative humidity conditions. Experimental design was completely randomized, with five replicates, each experimental unit consisting of a pot with five plants. Inoculation was done in the V2 growth stage (two fully expanded leaves), and the whorl of each plant received 2.0 mL suspension of 1.8 x 10(4) conidia mL-1 pathogen. The four used fungal isolates were obtained from infected crop residues at the municipalities Lages and Quilombo, Santa Catarina State, and Campinas do Sul and Vacaria, Rio Grande do Sul State. Disease severity was assessed at 21 days after inoculation in the V4 stage (four fully expanded leaves). No tested hybrid was totally resistant to the fungus S. macrospora. There was a significant difference in the disease severity between hybrids and fungal isolates. Hybrids inoculated with Quilombo isolate showed four reaction groups, while the isolates Vacaria, Lages and Campinas do Sul showed two groups. Some hybrids had varied behaviors against the isolates, suggesting different aggressiveness levels. There were hybrids that showed similar reaction to the isolates, suggesting greater stability for macrospora leaf spot.